Evolutionary and Regulatory Pattern Analysis of Soybean Ca2+ ATPases for Abiotic Stress Tolerance - Wang, Jian; Fu, Xujun; Zhang, Sheng; Chen, Guang; Li, Sujuan; Shangguan, Tengwei; Zheng, Yuanting; Xu, Fei; Chen, Zhong-Hua; Xu, Shengchun (Frontiers in Plant Science, 2022)
P2-type Ca2+ ATPases are responsible for cellular Ca2+ transport, which plays important roles in plant development and tolerance to biotic and abiotic stresses. However, the role of P2-type Ca2+ ATPases in stress response and stomatal regulation is still elusive in soybean. In this study, a total of 12 P2-type Ca2+ ATPases genes (GmCAs and GmECAs) were identified from the genome of Glycine max. We analyzed the evolutionary relationship, conserved motif, functional domain, gene structure and location as well as promoter elements of the family. Chlorophyll fluorescence imaging analysis showed that vegetable soybean leaves are damaged to different extent under salt, drought, cold, and shade stresses. Real-time quantitative PCR (RT-qPCR) analysis demonstrated that most of the GmCAs and GmECAs are up-regulated after drought, cold, and NaCl treatment, but are down-regulated after shading stress. Microscopic observation showed that different stresses caused significant stomatal closure. Spatial location and temporal expression analysis suggested that GmCA8, GmCA9, GmCA10, GmCA12, GmCA13 and GmCA11 might play a role in promoting stomatal closure under drought, cold and salt stress. GmECA1 might regulates stomatal closure in shading stress. GmCA1 and GmECA3 might have negative function on cold stress. The results laid an important foundation for further study on the function of P2-type Ca2+ ATPase genes GmCAs and GmECAs for breeding abiotic stress tolerant vegetable soybean.